A novel method for monitoring the cell surface expression of heteromeric protein complexes in dispersed neurons and acute hippocampal slices - Holman, David (2006)
The subunit composition of multimeric protein complexes is critical in determining their trafficking and functional properties. Despite there being multiple techniques to investigate the trafficking events of individual subunits there are currently limited means to monitor the trafficking properties of heteromeric protein complexes. Here, we combine surface biotinylation with co-immunoprecipitation to monitor the cell surface expression of native, heteromeric AMPA receptor complexes. Using this method, we demonstrate that the surface levels of GluR1/2 and GluR2/3 complexes are reduced following NMDA-evoked long-term depression (NMDA-LTD) in acute hippocampal slices. Finally, we discuss how this method can be adapted to monitor the cell surface expression of other heteromeric protein complexes.